2016
DOI: 10.1302/2058-5241.1.000032
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty and infection: how surgeons can reduce the risks

Abstract: Total joint arthroplasty (TJA) is one of the most common orthopaedic procedures. Nevertheless, several complications can lead to implant failure.Peri-prosthetic joint infections (PJI) certainly represent a significant challenge in TJA, constituting a major cause of prosthetic revision. The surgeon may have an important role in reducing the PJI rate by limiting the impact of significant risk factors associated to either the patient, the operative environment or the post-operative care.In the pre-operative perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 61 publications
0
19
0
2
Order By: Relevance
“…Periprosthetic joint infection occurs in 0.8-1.9% of patients after TKA [6]. Periprosthetic joint infection requires a long hospital stay incurring major costs, upsetting both the clinician and patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periprosthetic joint infection occurs in 0.8-1.9% of patients after TKA [6]. Periprosthetic joint infection requires a long hospital stay incurring major costs, upsetting both the clinician and patient.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al [7] reported that age, obesity, operation time, drain usage, diabetes mellitus, urinary tract infection, and rheumatoid arthritis were risk factors for periprosthetic joint infection. Ratto et al [6] reported that careful management of glucose level, general nutrition and body weight, as well as smoking cessation, reduced infection rates. However, Baker's cysts may disappear naturally after surgery and, even if they persist, no clinical manifestations are evident.…”
Section: Discussionmentioning
confidence: 99%
“…There are 3 main measures to minimize SSI, which include a series of preoperative, intraoperative, and postoperative measures. [ 10 , 11 ] Some medical comorbidities have been proven to be associated with increased risk of severe infection, predominantly including diabetes, obesity, rheumatoid arthritis, and immunosuppression. Particular measures must be adopted to control these comorbidities before proceeding with TJA to optimize the health of the patient and facilitate operative success.…”
Section: Discussionmentioning
confidence: 99%
“…Although most SSI prevention measures focus on the preoperative and intraoperative phases, the postoperative phase is also critical. Until the exudative and proliferative phases of wound healing are complete, the incisional edges are not fully sealed and the surgical incision remains vulnerable to exogenous bacterial contamination from the environment and substandard wound care . For example, lumbar spinal fusion surgery incisions may be close to the buttocks and perineum, and contamination from bedpans and commodes can pose an infection risk.…”
Section: A Bundle To Standardize the Incision Closure Processmentioning
confidence: 99%
“…Until the exudative and proliferative phases of wound healing are complete, the incisional edges are not fully sealed and the surgical incision remains vulnerable to exogenous bacterial contamination from the environment and substandard wound care. 39,54,88 For example, lumbar spinal fusion surgery incisions may be close to the buttocks and perineum, and contamination from bedpans and commodes can pose an infection risk. Body fluids, including blood and serum, that collect in the incision can provide a rich growth medium for any contaminating organisms.…”
Section: Postoperative Patient Instructionsmentioning
confidence: 99%